1996
DOI: 10.1002/mrm.1910350217
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the active B1 field in vivo

Abstract: The authors describe a method for accurate in vivo multislice imaging of the active component of the B1 field which is based on a previously proposed method, which uses the signal intensity ratio of two images measured with different excitation angles, and a repetition time TR 5 > or = 5 T1. The new method essentially reduces repetition and scan time by means of an additional compensating pulse. The suppression of T1 effects by this pulse are verified with simulations and measurements. Further investigations c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
339
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(343 citation statements)
references
References 14 publications
4
339
0
Order By: Relevance
“…For example, a three-angle set can be derived from four angles, as the smaller two angles are often within 1 point of each other and only one need to be retained. Ten angles optimized for TR ϭ 5 ms from a genetic algorithm (11) were also evaluated, consisting of the set 10␣ ' [2,3,4,5,7,9,11,14,17,22]. Although our straightforward strategy of combining appropriate ideal angles was not as sophisticated as these other approaches for multiple angle selection, we showed that comparable precision profiles could be achieved.…”
Section: Choice Of Flip Anglesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a three-angle set can be derived from four angles, as the smaller two angles are often within 1 point of each other and only one need to be retained. Ten angles optimized for TR ϭ 5 ms from a genetic algorithm (11) were also evaluated, consisting of the set 10␣ ' [2,3,4,5,7,9,11,14,17,22]. Although our straightforward strategy of combining appropriate ideal angles was not as sophisticated as these other approaches for multiple angle selection, we showed that comparable precision profiles could be achieved.…”
Section: Choice Of Flip Anglesmentioning
confidence: 99%
“…However, substantial inhomogeneity may arise when using separate transmit/receive coil systems or when imaging at field strengths above 1.5 T. An accurate approach to account for these variations is to map the B 1 ϩ field distribution using a double-angle method (16,17). Standard spin echo (SE) acquisitions are the most robust, as they are insensitive to B 0 variations, but are impractical in the clinic due to long scan times.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…For further quantitative assessment of the coil efficiency, the amplitude B 1xy was investigated by taking advantage of the principle of reciprocity (1,21). The B 1xy distribution was measured with a doubleangle approach utilizing a simple spin-echo sequence (30). Briefly, effects from longitudinal relaxation can be ignored if the repetition time is sufficiently long (T R Ն 5 T 1 ).…”
Section: In Situ Experiments On Phantomsmentioning
confidence: 99%
“…A high‐resolution GRE image was acquired to provide a reference for muscle segmentation (TR/TE = 100/3.45 ms, flip angle =10°, matrix 512 × 240, FOV 44 × 20.6 cm 2 ). B 1 maps were acquired with the double angle method11 (TE/TR = 11/7000 ms, FOV 44 × 20.6 cm 2 , 40 × 10 mm slices, nominal flip angles 60° and 120°), with B 1 error expressed as the percentage deviation of the actual flip angle from that nominally prescribed.…”
Section: Methodsmentioning
confidence: 99%